If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(w + -8) = 7(w + -2) Reorder the terms: 8(-8 + w) = 7(w + -2) (-8 * 8 + w * 8) = 7(w + -2) (-64 + 8w) = 7(w + -2) Reorder the terms: -64 + 8w = 7(-2 + w) -64 + 8w = (-2 * 7 + w * 7) -64 + 8w = (-14 + 7w) Solving -64 + 8w = -14 + 7w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-7w' to each side of the equation. -64 + 8w + -7w = -14 + 7w + -7w Combine like terms: 8w + -7w = 1w -64 + 1w = -14 + 7w + -7w Combine like terms: 7w + -7w = 0 -64 + 1w = -14 + 0 -64 + 1w = -14 Add '64' to each side of the equation. -64 + 64 + 1w = -14 + 64 Combine like terms: -64 + 64 = 0 0 + 1w = -14 + 64 1w = -14 + 64 Combine like terms: -14 + 64 = 50 1w = 50 Divide each side by '1'. w = 50 Simplifying w = 50
| -[4z-(12z+6)]=6+(7z+9) | | -3(w-3)-(7w-9)=-11w | | 600+3/4h=800 | | 4i=24 | | 6x+7-2x=4+3x-7 | | 4cos^2(x)-sin^2(2x)+5sin^2(x)=4 | | .90n=n+8 | | 6x^2-4y^2-12y-9=0 | | 100k=946 | | 12m=252 | | X^4+10x+169=0 | | 15n=960 | | 7(y-2)= | | 26n-25=1.22 | | -4x-1=5x+1+3 | | 3x+39-4x=2-9x+5 | | 6x-6-2x=8x-5 | | 4y+1=6y-3y | | -x+50=177 | | 2x+2-8=3x-21 | | 100n=750 | | .5x+3x+20=.5 | | 3n=945 | | 7y-2=0 | | 5x+2x=6x+8 | | 195=17-x | | x+4y=-36 | | 0.50(y+2)+0.333y=6 | | 560n=4250 | | 2.5z+5.2=3.8z | | 2n=294 | | -u+294=112 |